« Paysages de la vérité » du Chili durant l’Unité populaire (1970-1973) - Franck Gaudichaud (Cahiers des Amériques Latines)
More than thirty years after the fall of Salvador Allende’s government, we unquestionably have a distance criticizes in order to make re-appear certain landscapes of the truth of this conflict period of the Chilean history. However, today like yesterday, the researchers in social sciences being interested in the Popular Unit must face inevitable epistemological choices: several historiographic schools are still around the interpretation of this time Latin-American turning point. Based on a long bibliographical study, this article presents the principal interpretative tendencies of the thousand days of the Popular Unit. It recalls that if the theoretical approaches remain rather distinct according to the authors, the majority of the investigations were however dominated by a vision centred over the institutional field and the political parties. As, this text seeks to show all interest as there would be to operate «a return to social» and to study again all their place and their historicity with the social fights and the Chilean collective actions between 1970 and 1973.